ECONOMIC OUTLOOK OF YOUTH AND SPORTS ACTIVITIES IN TURKISH UNIVERSITIES - DEVECIOGLU SEBAHATTIN; EKENCİ GÜNER; MUSTAFA YILDIZ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The young population is the most dynamic and sensitive group in Turkey. The number of youth in the 12-24 age group constitutes 31 percent of the population in Turkey, which has a rather young population. Today, problems related to youth are among the important subjects dwelled upon on the agenda of Turkey. The expectations for the future of youth has been increasing gradually. The State engages in activities with the cooperation of national and international institutions, organizations and universities in order to determine the problems of the youth and to find solutions to these problems, within the framework of the economic, social and cultural structure. Significant progress has started to be made in recent years on the subject of the organization of youth by means of foundations, associations and youth organizations in the social and cultural fields. Social, cultural and sports activities aim to utilize Turkish University students time outside of class, to be interested in sports, to encourage sports doing, to organize sports activities in order to protect physical and mental health and to enable academic and administrative staff to benefit from sports services and facilities. Also, it is aimed to improve studies in sports by cooperation with domestic and international sports organizations and enable students to represent the university in sports events organized by the Turkey University Sports Federation. Moreover, it is aimed to operate facilities in a planned way and manage them from a single center for students, academic and administrative staff to benefit from all the sports facilities and materials of the university effectively. This research is done to determine Economic Outlook of youth and sports activities in Turkish Universities in a descriptive way. To proceed statistics of sport economy are used and economic structure of organizations related to and sports activities in World Universities as well as the financial movements of Turkish Universities are examined.